Hubungan antara Dukungan Sosial dengan Kinerja Pegawai PT Gresik Migas - Roghibah Nida’ Faradisi; Muhammad Ali Makki (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2022)
Social support is one of the things needed for employees in producing a good performance in their work, because social support can be related to employee performance. The formulation of the problem in this study is 1) is there a relationship between social support and employee performance at PT Gresik Migas, 2) how much social support is owned by PT Gresik Migas employees, 3) how much performance is owned by PT Gresik Migas employees. This type of research is a correlational study with quantitative data analysts, the population of this research is employees of PT Gresik Migas, with a research sample of 30 employees of PT Gresik Migas. Data collection techniques using observation and questionnaires/questionnaires. Analysis of the data used in this study is the Pearson Product Moment correlation formula. The results of the first study show the correlation coefficient rxy = 0.855, this figure indicates a perfect level of positive correlation between social support and employee performance. Meanwhile, from hypothesis testing, it is known that the value of sig (0.000) <0.05 so that the hypothesis in this study can be accepted and proven, which means that social support has a relationship with employee performance. The second and third results show that employees of PT Gresik Migas have an average social support and moderate performance with a percentage of 80% and 80.6%, respectively.